Differentiating with brand personality in economy hotel segment. (October 2014) - Li, Xiangping; Yen, Chih-Lun (Alan); Uysal, Muzaffer
The purpose of this study is to explore the applicability of brand personality in the economy hotel segment and whether hotel brand personality could differentiate between similar hotel brands. Courtyard and Hampton Inn are used in this study. The results of this study suggest that brand personality dimensions can be clearly delineated in the economy hotel sector, in consistent with Aaker's dimensions, ruggedness, competence, excitement, sophistication, and sincerity. Moreover, similar hotel brands can be perceived differently based on their personalities. Additionally, although common brand personality factor structure can be used to describe economy hotel brands in general, specific hotel brand does exhibit some unique dimensions.